A Nationwide Survey On Malaysian Hospital Physicians’ Practices of Intravenous Potassium Chloride Supplementation and Opinions On Premixed Formulation In The Treatment Of Hypokalaemia. - Chee, Ping Chong; Melissa, Mohammad Hirman (Penerbit Universiti Sains Malaysia, 2023)
This study aims to evaluate the Malaysian hospital physicians’ practices of intravenous potassium chloride in the treatment of hypokalaemia and their opinions on using premixed formulation. This was a nationwide online survey using a self-administered questionnaire. The survey link was sent to the practising hospital physicians in Malaysia through email (n = 1,455), Facebook Messenger (n = 2,734) and posted on Facebook as well. A total of 207 responses were received. The physicians were mostly males (63.8%), aged between 30 years old–39 years old (51.2%) and worked in the government sectors (76.8%). The most preferred dosage of potassium chloride for mild, moderate and severe hypokalaemia was 10 mmol (44.4%), 20 mmol (55.1%) and 30 mmol (37.7%), respectively. The mostly chosen infusion rate of potassium chloride for mild hypokalaemia was over 24 h (41.1%) while for both moderate and severe hypokalaemia were over 1 h–2 h (63.8% and 89.9%, respectively). The concentration of intravenous potassium chloride is the main factor (68.1%) which would influence the infusion route choice. Serum potassium monitoring of every 24h was chosen by 52.7% of the respondents for mild hypokalaemia while every 1 h–2 h was mostly chosen for moderate and severe hypokalaemia (49.3% and 87.4%, respectively). Cardiac monitoring was mostly opted in severe hypokalaemic patients (70.0%). Majority of physicians agreed that a premixed formulation is easier to administer (64.7%) and safer for the patients (51.7%). In conclusion, there were variations in the prescribing practices among Malaysian physicians to treat hypokalaemia. Most physicians were in favour of premixed formulation.